Controlling the Capital Political Dominance in the Urbanizing World - Goodfellow, Tom; Jackman, David (Oxford University Press, 2023)
Authoritarianism is on the rise globally, with more than twice as many countries experiencing democratic decline as democratic enhancement in recent years. This has been occurring simultaneously with unprecedented rates of urbanization in many parts of the world, raising questions about the role of cities-often considered the focal points of democratic deepening-in this authoritarian turn. With most literature on authoritarianism focusing on the national scale, in this book we train our gaze on capital cities, which as 'containers' of both capital and sovereignty are spaces in which authoritarian dominance is increasingly built, contested, maintained, and undone. Focusing on some of the world's fastest urbanizing regions in sub-Saharan Africa and South Asia, the book explores the multiple ways in which authoritarian regimes have been attempting to build and sustain long-term dominance in capital cities in order to meet the challenge of urban political resistance. Our diverse selection of case studies spans governing regimes that have recently tried to build urban dominance and spectacularly failed, as well as those that have managed to hold onto power by constantly evolving strategies for dominance that limit the potential for urban opposition to tip into regime overthrow. With chapters on Addis Ababa, Colombo, Dhaka, Harare, Kampala, and Lusaka, this book offers the first cross-regional comparative study of the relationship between cities and political dominance. It contributes to debates on authoritarianism and authoritarian durability, urbanization, political contestation and resistance, the politics of development, and the prospects for democracy.